Marine micro-phytoplankton of Singapore, with a review of harmful microalgae in the region - Toh, Hii Tan; Chui, Pin Leaw; Chee, Sandric Yew Leong; Lay, Peng Lim; Siew, Moon Chew; Sing, Tung Teng; Po, T.L (National University of Singapore, 2016)
A survey of marine phytoplankton in the Singapore Strait was carried out between May and June 2013, as part of an effort to determine the diversity of phytoplankton in Singapore’s coastal waters. A total of 34 microalgal samples were collected using a 20 μm-mesh plankton net and from coastal sediments. Living samples and preserved samples in Lugol’s solution were identified to species as far as possible under the microscope. A checklist of marine micro-phytoplankton was updated to encompass 270 taxa, including 49 new records from Singapore waters. Some 37 species from 15 families were dinoflagellates, and 233 species from 50 families were diatoms. Harmful microalgae, categorized as biotoxin-producers and fish killers, were also found in this survey. These were in the genera Alexandrium, Amphidinium, Ceratium, Cochlodinium, Coolia, Dinophysis, Gambierdiscus, Karenia, Karlodinium, Ostreopsis, Prorocentrum, Nitzschia, and Pseudo-nitzschia.